The Atlantic spiny lumpsucker Eumicrotremus spinosus: life history traits and the seemingly unlikely interaction with the pelagic amphipod Themisto libellula - Berge, Jørgen; Nahrgang, Jasmine (Polish Polar Research, 2013)
During a cruise to Svalbard in September 2012 a unique collection of the little known but widely distributed Atlantic spiny lumpsucker (Eumicrotremus spinosus) was made in the Hinlopen Strait. A total of 140 individuals (36–101mm total length) were col− lected using a bottom trawl. All individuals were sexed and 26 of these were also analysed for gonadosomatic index (GSI), hepatosomatic index (HSI) and stomach content. The sex ratio of the entire sample showed a strong bias towards females (75% of all examined speci− mens). The GSI ranged from 1.4 to 5.8% except for one female with a GSI of 20%. All fe− males carried gonads in which eggs were clearly visible, independent of size, indicative of an early sexual maturation and an iteroparous life cycle of females. All examined specimens had almost an exclusively pelagic diet, with Themisto libellula constituting 100% of the stomach content in 80% of the examined fishes. The results are discussed in relation to diel vertical migration of Arctic zooplankton and deep migrating layers.